The effect of C:N:P ratio, volatile fatty acids and Na+ levels on the performance of an anaerobic treatment of fresh leachate from municipal solid waste transfer station - Ghasimi, Seyed Mohammad Dara; Idris, Azni; Chuah, Teong Guan; Tey, Beng Ti (Academic Journals, 2009)
Anaerobic digestion was carried out in this study to treat fresh leachate from municipal solid waste transfer station in a 10 L stirred tank reactor (STR). The treatment process was performed in batch and semi-continuous process. Palm oil mill effluent (POME) sludge was used as an inoculum. A high BOD reduction was achieved in 3 different treatment conditions in this study. A BOD removal of 85, 77 and 90% for the batch (Experiment 1), semi-continuous process without pH adjustment (Experiment 2) and semi-continuous process with pH adjustment (Experiment 3), respectively were recorded. It was observed that there was no significant deficiency in required nutrients for Experiment 1, 2 and 3 in this work. High concentration of volatile fatty acids (VFAs) was detected in Experiment 3, which indicated the instability of bioreactor in which lower methanogenic activity was observed. The levels of acetic acid (HAc) and propionic acid (HPr) appeared to be the VFA species that accumulated and started to cause an imbalance in the reactor. It was found that the use of large amount of sodium hydroxide (NaOH) to adjust the bioreactor pH had caused an inhibition of the metabolic activity of methanogenesis bacteria that involved in the methane production.